The Dynamics of Social Institutions in Family Law: Understanding Values, Norms, and Their Functions - Lagus, Wegestin; Salma, Salma; Bakhtiar, Bakhtiar (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
Social institutions are systems of norms, values, and behavioral patterns that regulate community life, including family law. Modernization and globalization have driven shifts in social norms and values, influencing practices in family law, particularly in marriage, inheritance, and child custody. These shifts create tensions between traditional norms and social changes, with implications for the stability of family law. This study contributes by highlighting three core aspects of social institutions within family law: elements, functions, and substance. Using a qualitative approach through literature review of academic sources, the study identifies key elements of social institutions, norms, institutions, symbols, and social sanctions; their functions as social control mechanisms, identity formation for families, and safeguards of social order; as well as their substantive values of justice, responsibility, and harmony that shape standard behavioral patterns within families. Accordingly, this study emphasizes that understanding the dynamics of elements, functions, and substance of social institutions is essential for ensuring that family law remains adaptive to social change without losing its foundational values.